Selection of terminal Piétrain pigs improves vitality and prevalence of congenital defects in crossbred piglets - Gorssen, Wim; Winters, Carmen; Meyermans, Roel; Chapard, Léa; Hooyberghs, Katrijn; De Kort, Jaro; Van den Broeke, Alice; Depuydt, Jürgen; Janssens, Steven; Buys, Nadine (Frontiers in Animal Science, 2025)
Reducing piglet mortality and congenital defects is vital in pig production, as these traits substantially impact piglet welfare and lead to significant production losses. Additionally, piglets born with congenital defects often demand extra attention and resources from pig farmers. Nowadays, most breeders have shifted towards a more balanced breeding within their maternal pig lines, with a focus on both reproductive capacity and survival traits. However, few studies have investigated the influence of paternal sire genetics on crossbred piglets’ vitality and congenital defects. In this study, we evaluated the impact of an ongoing Piétrain sire breeding program on these traits in crossbred piglets that started in 2019. This study was based on two unique datasets with litter records collected between 2016 and 2024 on four independent commercial sow farms. The first dataset was collected by the breeding organization and consisted of 12,010 crossbred litters (Piétrain sire, hybrid dam; two farms) scored on piglets’ vitality, number of piglets with porcine congenital splay leg syndrome and scrotal hernia, pre-weaning mortality and the number of piglets born death. A second dataset (5,380 crossbred litters; two farms) was collected by ILVO (Flanders Research Institute for Agriculture, Fisheries and Food), using 426 Piétrain boars common to the first dataset of the breeding organization. Using a genetic sire-dam model, the studied traits were estimated to be lowly heritable (h2 = 5.2 to 15.6%). Moreover, vitality scores were genetically moderately correlated with preweaning mortality (rg=-0.59) and porcine congenital splay leg syndrome (rg=-0.52). Evolutions of phenotypic records and estimated breeding values since the start of the breeding program indicate a positive impact on piglet survival and prevalence of porcine congenital splay leg syndrome. The observed prevalence for porcine congenital splay leg syndrome roughly halved from ±1% in 2019 to ±0.5% in 2024, while for pre-weaning mortality, the observed prevalence dropped from ±17% in 2019 to ±14% in 2024. A joint analysis of the datasets showed a moderate to high genetic correlation (rg=0.52 to 0.84) for porcine congenital splay leg syndrome and pre-weaning mortality, indicating the translatability of estimated breeding values for terminal sires to new farms, specifically for these traits. In conclusion, these results show that paternal pig breeding programs can be effective in substantially improving piglets’ vitality while reducing porcine congenital splay leg syndrome and pre-weaning mortality. Due to the pressing societal demands for more animal welfare and the economic impact of these traits, we show other pig breeding companies the important role of paternal pig genetics towards improved piglet vitality and a reduction of congenital defects.